ZBEU'S Greenmetric Perspective - Yildirim, Yılmaz; Karaelmas, Deniz (Universitas Diponegoro, 2023)
Environmental and sustainability issues are becoming increasingly important as rapidly advancing technology damages the environment and a growing world population depletes natural resources. UI GreenMetric draws attention to environmental and sustainability issues in higher education institutions, which are expected to provide research solutions to important global challenges. As a result of sustainability studies, sustainable and green campuses Zonguldak Bülent Ecevit University, which plans and manages its formation, aims to be a university that contributes to sustainable life as an